2017
DOI: 10.1177/0021998317737831
|View full text |Cite
|
Sign up to set email alerts
|

Frequency optimization of laminated functionally graded carbon nanotube reinforced composite quadrilateral plates using smoothed FEM and evolution algorithm

Abstract: The paper presents an efficient numerical optimization approach to deal with the optimization problem for maximizing the fundamental frequency of laminated functionally graded carbon nanotube-reinforced composite quadrilateral plates. The proposed approach is a combination of the cell-based smoothed discrete shear gap method (CS-DSG3) for analyzing the first natural frequency of the functionally graded carbon nanotube reinforced composite plates and a global optimization algorithm, namely adaptive elitist diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 71 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…In these fields, various optimization studies have been carried out to maximize the performance of these structures while reducing cost [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Vo-Duy et al [24,25] presented the weight minimization and natural frequency maximization problems of laminated plates using an adaptive elitist differential evolution algorithm treating the ply thicknesses, fiber orientations, and the fiber volume fractions as the variables of optimization. As the constraint of optimization, the first fundamental frequency of the laminated plate was kept above a certain lower bound in every iteration.…”
Section: Introductionmentioning
confidence: 99%
“…In these fields, various optimization studies have been carried out to maximize the performance of these structures while reducing cost [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Vo-Duy et al [24,25] presented the weight minimization and natural frequency maximization problems of laminated plates using an adaptive elitist differential evolution algorithm treating the ply thicknesses, fiber orientations, and the fiber volume fractions as the variables of optimization. As the constraint of optimization, the first fundamental frequency of the laminated plate was kept above a certain lower bound in every iteration.…”
Section: Introductionmentioning
confidence: 99%
“…An edge-based smoothed FEM was proposed for static eigenvalue assessment of 2D piezoelectric structures [54]. An effective numerical method was presented to optimize and maximize the basic frequency of functionally graded carbon-nanotube-strengthened four-sided sheets [55]. On the commercial software ABAQUS, Bhowmick and Liu established a phase-field model based on cellbased smoothed FEM (CSFEM) to address the brittle fracturing in solids [56].…”
Section: Introductionmentioning
confidence: 99%
“…In [19], Vo-Duy T et al suggested a global numerical approach for lightweight design optimization of laminated composite plates subjected to frequency constraints by applying aeDE. Moreover, in [20], this author also proposed an aeDE based-effective approach to maximize the fundamental frequency of laminated functionally graded carbon nanotube-reinforced composite quadrilateral plates. Besides, in [21], Demertzis K and liadis L utilized aeDE to optimize extreme learning machine model, and then it is applied to create an advanced computer vision system for the phenotype based automatic recognition of invasive or other unknown species.…”
Section: Introductionmentioning
confidence: 99%